Fabrication and visible-light photocatalytic properties of nano-Ag10Si4O13. Issue 22 (15th November 2021) - Li, Cuixia; Zhang, Youyou; Jin, Haize; Kang, Weichao; Kong, Wenhui; Li, Wensheng
Abstract: Agx Siy Oz has the potential to inhibit the recombination of photoinduced electron hole pairs via an internal electric field induced by asymmetrical Si–O tetrahedral chains. The strength of the [SiO4 ] tetrahedral produces a very strong internal electric field for Ag10 Si4 O13 . Here, a novel and convenient synthetic strategy for nano-Ag10 Si4 O13 based on a sol-gel method is proposed. A small band gap, an internal electric field and a small size ensure good efficiency for nano-Ag10 Si4 O13 during all chemical dynamical processes, including charge excitation, charge separation and charge transfer.